Responsible leadership in Singapore - Chew, Jinming (2022)
The recent trend in sustainability globally and Singapore Green Plan 2030 have resulted in a need for responsible leaders in Singapore to drive these new initiatives. Leadership complexity is well recognized and with the lack of substantial research in responsible leadership, especially in Singapore context, an exploratory research is conducted to understand the perceptions of the attributes of a responsible leader in Singapore mediating through the stakeholder theory lens. The research aims to address three main questions: How responsibility is perceived by people with different demographic? How does the perceptions of corporate responsibility affect responsible leadership? What are the common attributes which a responsible leader should possessed? This exploratory research is done by using mix methods which incorporate both qualitative and quantitative elements to obtain new perspectives on this topic. An online survey is conducted through distribution among friends, school mates, colleagues and relatives residing and working in Singapore and redistributed to their friends and colleagues. Qualitative data obtained is coded distinctly and quantified. Thereafter, all data is analysed by using STATA or excel. The results show some difference in different demographics and contexts on the perceived attributes of a good leader. Perceived attributes of a responsible leader are derived from a combination of individual and corporate construct through the perception of relative importance of relevant stakeholders. The ten key attributes identified are competency, visionary, empathy, motivating, integrity, mentoring, leading by example, accountable, awareness and fair. These attributes can be cultivated into the next generation of leaders to groom future responsible leaders to drive sustainability initiatives. The construct can also be used a basis for future research pertaining to responsible leadership.